Flame retardant polyesters. I. Phosphorous flame retardants - Yang, Seung-Cheol; Kim, Jae Pil (Journal of applied polymer science, 2007)
Commercially available two types of phosphorous flame retardants (FRs) for polyester were compared from the viewpoint of chemical reactivity, reaction mechanism, and byproduct formation. 3-(Hydroxyphenyl phosphinyl) propanoic acid (HPP) and 9,10-dihydro-9-oxa-10-2,3-dicarbonylpropyl)-10-phosphophenanthrene-10-oxide (DI) were used as a main chain type and a pendant type, respectively. HPP and DI showed different behavior with ethylene glycol (EG). More acidic HPP reacted with EG spontaneously and then produced esterified terminal hydroxy end group reacted with EG to form terminal diethylene glycol (DEG) end group. But the composition in the HPP solution was not varied for a long time below the esterification temperature. Contrast to HPP, DI showed normal esterification procedure. DI esterified with EG to form DI ester of EG, and DEG formation is not distinct. The difference of reactivity and DEG formation is caused by the difference of acidity in EG solution. For production of phosphorous containing polyester, it is desirable that HPP is introduced into the reactor in the mere solution state and DI in the esterified state. In addition, for production of polyester having the same phosphorous content in commercial scale, it is more beneficial to apply HPP than DI because of low input of FR due to low molecular weight. © 2007 Wiley Periodicals, Inc. J Appl Polym Sci, 2007